Строение и функции кожи летательных перепонок рукокрылых (Vespertilionidae, Chiroptera) - Ковалева, И.М. (Вестник зоологии, 2008)
Опубликованные до сих пор данные о строении кожи летательных перепонок рукокрылых содержат много противоречивых сведений отноcительно отдельных структур. Автором проведены исследования микроморфологического строения кожи летательных перепонок Nyctalus noctula и Eptesicus serotinus с точки зрения выполнения этой структурой терморегуляторной и респираторной функций. The data published till now about the constitution of the flying membrane skin in bats contain many contradictory items of information concerning individual structures. The author conducts researches in micromorphological constitution of the skin of flying membranes Nyctalus noctula and Eptesicus serotinus (Chiroptera), from the point of view of performing heat regulating and respiratory functions.